Caregiver burden and its associated factors among primary caregivers of stroke survivors at Amhara regional state tertiary hospitals: a multicenter study - Gebremariam Bekele; Melisew Mekie Yitayal; Yihalem Belete; Yisak Girma; Tesfa Kassa; Yohannes Awoke Assefa; Solomon Gedlu Nigatu; Getachew Azeze Eriku (Frontiers in Stroke, 2023)
BackgroundCaregivers of stroke survivors play a crucial role in post-stroke functional recovery and the prevention of complications. Although the situation is incredibly stressful and intimidating and the caregiver burden is high, there is little evidence in the local Ethiopian context of the extent of the burden among caregivers of stroke survivors. Therefore, the aim of this study was to assess the level of caregiver burden and its associated factors among primary caregivers of stroke survivors in Ethiopia.MethodsA cross-sectional study was conducted in Amhara regional state tertiary hospitals from April to June 2022. A standardized questionnaire was used to record factors associated with caregiver burden, including sociodemographic, clinical, and care situation factors. The Zarit caregiver burden interview (short form) was used to assess the level of caregiver burden. A systematic random sampling method was employed to select the study participants. Multinomial logistic regression was employed to identify the potential factors associated with the level of caregiver burden.ResultsThe overall prevalence burden among primary caregivers of stroke survivors was 67%. 61.1% had a mild to moderate burden, while 5.9% had a severe burden. In multivariable multinomial logistic regression analysis, sex, household income, duration of care, and duration of caregiving hours per day were factors significantly associated with the level of burden among caregivers of stroke survivors.ConclusionsBeing female, having a low household income, caring for more than 3 months, and caring for more than 6 h per day were factors significantly associated with the burdens of the primary caregivers of stroke survivors. It is better: health care providers must recognize and screen for burdens and provide special attention.